Apartheid policy in South Africa - Azi Ayubi (GoAcademica Research & Publishing, 2023)
Racial discrimination is a very big problem and is found in several countries such as the United States, Great Britain and the most dominant in South Africa with the policy of apartheid. Therefore, South Africa is at the center of the fight against racism towards achieving justice. The word apartheid means